Therapeutic applicability of helminths in autoimmune diseases – literature overview - Jacek Zwiernik; Tomasz Arłukowicz; Beata Zwiernik; Tomasz Matyskieła; Marta Gimeła-Dargiewicz; Agnieszka Rakowska; Beata Januszko-Giergielewicz; Ewa Rotkiewicz (Gastroenterology Review)
This paper presents an overview of published studies conducted on helminths – parasites of the human gastrointestinal tract. Making use of their ability for immunomodulation may lead to the introduction of effective therapies for autoimmune diseases. This paper presents chronologically attempts to treat autoimmune diseases not only of the gastrointestinal tract, but also of the nervous and endocrine systems, which have been undertaken for decades. The overview of analysed reports demonstrates that as medical knowledge on the cells and mediators participating actively in inflammatory processes accumulates, clinical trials focus on ever more specific areas concerning the pathomechanisms of autoimmune diseases. The outcomes of clinical trials conducted both on animals and humans give reasons to assume that the modification of the human intestinal microflora may be the key to fighting against these diseases.